Sistem Informasi Rute Jalur Bus Beserta Tarif Berbasis SmsService dengan Gammu Sms Gateway pada Batik Solo Trans (BST) - Ningsih, Eka Wintia, Nurgiyatna, ST., MSc., PhD (2016)
Information system about Batik Solo Trans (BST) routes based on sms gateway which take care of costumers choosing the route. Batik Solo Trans (BST) had much of routes that is complicate to choose the right one. For foreigner or university student who new in the city. They should know which way to go to reach their destination. The website help to inform the routes use geography maps. The sms, run command in according with the system that has been made to inform the costumer's destination. These program made by using software Gammu, Xampp, MySQL and programming language PHP, HTML. The system was tested by using a questionnaire to the DISHUB and passenger of BST. Tests carried out questionnaires to 25 respondents. The test result of the questionnaire obtained by 88% saying that the system feasible and help in finding the destination